Emerging research on applied fuzzy sets and intuitionistic fuzzy matrices - Adak, Amal Kumar 1992-; Manna, Debashree 1987-; Bhowmik, Manoranjan (Advances in computational intelligence and robotics (ACIR) book series, 2017)
This book is a pivotal reference source for the latest scholarly perspectives on the interdisciplinary use of fuzzy logic theory, focusing on the application of sets and matrices by highlighting theoretical framework and empirical research findings